ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI LOYALITAS PELANGGAN INDOSAT OOREDOO PADA MAHASISWA UNIVERSITAS BENGKULU - Ricky Ramadhan; Lizar Alfansi; Sularsih Anggarawati (UNIB Press, 2021)
The purpose of this research is to find out the factors that influence customer loyalty: service quality, perceived switching costs, trust, customer satisfaction, perceived value, corporate image of Indosat Ooredoo customer loyalty to Bengkulu university students. The populations in the study were students of the Bengkulu University consist of 100 respondents. The accidental sampling method is used. Descriptive statistics and multiple regression linear analysis, test t, and test f are used to analyze the data. The results showed that the service quality, perceived switching costs, trust, customer satisfaction, perceived value, corporate image have a positive effect on Indosat Ooredoo customer loyalty to Bengkulu University Students. the meaning, if the Good quality service increased customer loyalty if the perceived switching cost of high customer loyalty will increase If trust increases customer loyalty will increase if the perceived value increases customer loyalty will increase and if the corporate image is good then customer loyalty will increase as well.